An introductory guide to conducting the Trier Social Stress Test. (December 2019) - Labuschagne, Izelle; Grace, Caitlin; Rendell, Peter; Terrett, Gill; Heinrichs, Markus
Highlights: The Trier Social Stress Test (TSST) is a robust tool to induce acute psychobiological stress. Yet, clear methodological guidelines for conducting the TSST are not available. We provide an accessible step-by-step introductory guide for conducting the TSST. These guidelines may be modified depending on to the individual research question. We hope to provide a valuable resource for researchers and improve the scientific standard in this field of research. Abstract: The Trier Social Stress Test (TSST) is a reliable biopsychological tool to examine the effects of acute stress on psychological and physiological functioning in humans. While the TSST reliably increases hypothalamic-pituitary-adrenal axis activation, amongst other biomarkers, through a combination of social evaluative threat and uncontrollability, the original protocol is limited in methodological detail that has impacted its reproducibility. Although many studies include a mock job interview and surprise arithmetic task, there are large variations in the timing of events, the number and method of biological (e.g., cortisol) sampling, the administration of a glucose drink, set-up of equipment and rooms, panel composition, and panel interaction with participants. We provide an overview of the potential impact of methodological variations on the stress (cortisol) response. Importantly, we also provide a step-by-step guide as a laboratory manual on how to conduct the TSST. This introductory guide may be a useful and time-saving resource that may also improve the scientific standard and reliability of the reported psychobiological stress effects in future studies.